Eksternalitas Kebijakan Standar Keselamatan Perkeretaapian di Kota Pariaman - Rafelia Putri Hidayat (Lembaga Yasin AlSys, 2026)
Railway safety is an important aspect of the public transportation system, particularly at level crossings that have a high risk of accidents. In Pariaman City, especially at the Simpang Lohong crossing, the implementation of railway safety standard policies has not been optimal and has generated various external impacts on the community. This study aimed to analyze the forms of externalities arising from the implementation of railway safety standard policies and to identify the supporting and inhibiting factors in their implementation. This study used a descriptive qualitative approach. Data were collected through interviews, observation, and documentation studies. The research informants were selected using purposive sampling, involving PT Kereta Api Indonesia, the Pariaman City Transportation Agency, Balai Teknik Perkeretaapian Class II Padang, as well as local communities and road users. The results showed that there were three forms of externalities, namely ownership externalities, technical externalities, and public goods externalities. Ownership externalities were characterized by the suboptimal division of authority among institutions, technical externalities were reflected in limited facilities and undisciplined road-user behavior, while public goods externalities were indicated by low public awareness in using and maintaining safety facilities. Supporting factors for policy implementation included clear regulations, the availability of facilities, and the active role of relevant institutions. Meanwhile, inhibiting factors included budget limitations, administrative constraints, limited human resources, and low public awareness. The conclusion of this study emphasizes that the implementation of railway safety policies in Pariaman City has not been fully effective and still requires comprehensive improvement through strengthening institutional coordination, optimizing safety facilities, and increasing public awareness. These findings imply the importance of more integrated level-crossing safety governance within the framework of public transportation policy.